Cognitive state following mild stroke: A matter of hippocampal mean diffusivity. Issue 2 (18th August 2015) - Kliper, Efrat; Ben Assayag, Einor; Korczyn, Amos D.; Auriel, Eitan; Shopin, Ludmila; Hallevi, Hen; Shenhar‐Tsarfaty, Shani; Mike, Anat; Artzi, Moran; Klovatch, Ilana; Bornstein, Natan M.; Ben Bashat, Dafna
ABSTRACT: The hippocampus is known to play a vital role in learning and memory and was demonstrated as an early imaging marker for Alzheimer's disease (AD). However, its role as a predictor for mild cognitive impairment and dementia following stroke is unclear. The main purpose of this study was to examine the associations between hippocampal volume, mean diffusivity (MD) and connectivity and cognitive state following stroke. Eighty three consecutive first ever mild to moderate stroke or transient ischemic attack (TIA) survivors from our ongoing prospective TABASCO (Tel Aviv Brain Acute Stroke Cohort) study underwent magnetic resonance imaging scans within 7 days of stroke onset. Hippocampal volume was measured from T1 weighted images, hippocampal mean diffusivity was calculated from diffusion tensor imaging and connectivity was calculated from resting state fMRI. Global cognitive assessments were evaluated during hospitalization and 6 and 12 months later using a computerized neuropsychological battery. Multiple linear regression analysis was used to test which of the hippocampi measurements best predict cognitive state. All three imaging parameters were significantly correlated to each other (| r 's| >0.3, P's  < 0.005), and with cognitive state 6 and 12 months after the event. Multiple regression analyses demonstrated the predictive role of hippocampal mean diffusivity (β = −0.382, P  = 0.026) on cognitive state, above and beyond that of volume and connectivity of this structure. To our knowledge, the combination of hippocampal volume, mean diffusivity and connectivity in first ever post stroke or TIA patients has not yet been considered in relation to cognitive state. The results demonstrate the predictive role of hippocampal mean diffusivity, suggesting that these changes may precede and contribute to volumetric and connectivity changes in the hippocampi, potentially serving as a marker for early identification of patients at risk of developing cognitive impairment or dementia. © 2015 Wiley Periodicals, Inc.